Psychosocial deprivation, executive functions, and the emergence of socio-emotional behavior problems - McDermott, Jennifer M.; Troller-Renfree, Sonya V.; Vanderwert, Ross; Nelson, Charles A.; Zeanah, Charles H.; Fox, Nathan (Frontiers in Human Neuroscience, 2013)
Early psychosocial deprivation can negatively impact the development of executive functions (EF). Here we explore the impact of early psychosocial deprivation on behavioral and physiological measures (i.e. event-related potentials; ERPs) of two facets of EF, inhibitory control and response monitoring, and their associations with internalizing and externalizing outcomes in the Bucharest Early Intervention Project (BEIP; Zeanah et al., 2003). This project focuses on two groups of children placed in institutions shortly after birth and then randomly assigned in infancy to either a foster care intervention or to remain in their current institutional setting. A group of community controls was recruited for comparison. The current study assesses these children at 8-years of age examining the effects of early adversity, the potential effects of the intervention on EF and the role of EF skills in socio-emotional outcomes. Results reveal exposure to early psychosocial deprivation was associated with impaired inhibitory control on a flanker task. Children in the foster care intervention exhibited stronger response monitoring compared to children who remained in the institution on the error-related positivity (Pe). Moreover, among children in the foster care intervention those who exhibited stronger error-related negativity (ERN) responses had lower levels of socio-emotional behavior problems. Overall, these data identify specific aspects of EF that contribute to adaptive and maladaptive socio-emotional outcomes among children experiencing early psychosocial deprivation.